2015
DOI: 10.1177/1049909115574491
|View full text |Cite
|
Sign up to set email alerts
|

Essential Elements of an Effective Prison Hospice Program

Abstract: As the number of prison inmates facing end-stage chronic illness grows, more prisons across the U.S. must address the need for end-of-life care. Many will likely need to develop a plan with potentially limited resources and external support. This case study presents one long-running model of care, the Louisiana State Penitentiary Prison Hospice Program. Based on field observations and in-depth interviews with hospice staff, inmate volunteers and corrections officers, we identify five essential elements that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 28 publications
1
73
0
Order By: Relevance
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The review identified 23 articles, 16 reporting qualitative methods2 3 29–42(table 3), six reporting quantitative methods8 9 43–46(table 4) and one reporting mixed methods4(table 3). Methodological diversity was high across all groups.…”
Section: Resultsmentioning
confidence: 99%
“…Two qualitative studies only reported their methodological approach as ‘qualitative’ 2 40. Thirteen articles reported findings from six studies based in the USA,8 9 29–33 36 39–43 four articles reported findings from three studies based in the UK,4 35 38 45 three articles reported findings from two studies based in Switzerland,3 34 37 two articles reported findings from one study in France2 46 and one article reported findings from a study in India 44. The articles reported on a broad range of areas, including prison healthcare facilities,43 45 the health of dying prisoners and causes of death,8 9 44 46 elderly and dying prisoners views on issues related to palliative and end of life care in prisons3 4 34 36 40 and inmate volunteer caregivers 30–33 42.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, there were 69 prison-based hospice programs in the U.S., many based on the system at Louisiana State Penitentiary. 5 The hospice program at Louisiana State Penitentiary has been in operation since 1998, caring for 227 patients between 1998 and 2014. The program is a ''peer-care model,'' whereby trained inmate volunteers provide much of the care, including assistance with activities of daily living, monitoring of symptoms, and providing social and spiritual support.…”
Section: Commentmentioning
confidence: 99%
“…These guidelines highlight the increasing call from the medical community to provide compassionate end-of-life care to prison populations. 5,6 Encouragingly, prison-based hospice units have been found to generally follow the Guiding Responsive Action for Corrections in End-of-Life Care project guidelines, although there is variation among units with respect to visitation policies and opioid use. 6 This progress notwithstanding, there continue to be few correctional institutions with hospice facilities and most prisoners continue to use community hospitals for end-of-life care.…”
Section: Commentmentioning
confidence: 99%